Reversible humidity-responsive sensing fiber and preparation method and application thereof

CN122980070APending Publication Date: 2026-10-27DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611469160.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

以期在常规室温干燥条件下,构建一种兼顾微纳贯通孔隙与高强融合节点骨架的新型纤维,克服现有湿度传感纤维的灵敏度和力学性能无法兼顾的难题,以期推动这类智能纤维材料与相关电子织物的发展与技术进步,为这类材料走向应用奠定基础、提供新方法

Benefits of technology

[0035](1)向列相液晶诱导的致密取向结构克服了传统气凝胶纤维力学短板:本发明芯层引入具有流体学预取向特性的向列态MXene分散液,结合湿纺过程中的喷丝针头内及出口处的剪切取向作用与动态牵伸作用,高效诱导芯层MXene纳米片与大分子链沿轴向高度取向排列。这种取向结构不仅构建了连续的电子隧穿路径,更赋予了纤维较高的拉伸强度,弥补多孔类传感纤维受力易断的致命缺陷,满足严苛的纺织加工需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980070A_ABST
    Figure CN122980070A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of reversible humidity response sensing fiber and its preparation method and application, comprising: aramid fiber is dissolved in solvent system, and shell layer spinning solution is obtained;Liquid dispersion of nematic MXene, cellulose derivative aqueous solution containing substituted side group and solvent are mixed, and core layer spinning solution is obtained;Shell layer spinning solution and core layer spinning solution are coaxially wet spinning, and post-processing, and humidity sensing fiber is obtained;Wherein the coagulation bath used in coaxial wet spinning is borate aqueous solution.The present application realizes humidity sensing fiber with excellent mechanical properties, high sensitivity sensing ability and sensing reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional fibers, and specifically relates to a reversible humidity-responsive sensing fiber, its preparation method, and its application. Background Technology

[0002] With the rapid development of IoT technology and flexible electronics, smart wearable devices are showing tremendous application demand in fields such as sports monitoring, health monitoring, and smart healthcare. Flexible electronic fabrics, with their inherent breathability and comfort, have received widespread attention and research in recent years as an ideal carrier for smart wearable devices. Flexible electronic fibers, as the basic building blocks of electronic fabrics, can be used to construct electronic fabrics with different functions through weaving, knitting, and sewing, enabling responses or sensing functions such as temperature, humidity, and strain. Among these, humidity-sensing fibers have significant application needs in areas such as monitoring human sweat, detecting respiratory rate, sensing wound exudate, and providing environmental humidity warnings, making them one of the hottest research topics in the field.

[0003] Currently, the main method for preparing humidity-sensing fibers involves combining nano-conductive fillers (such as carbon nanotubes, graphene, metal nanowires, MXene, etc.) with hygroscopic polymer materials (such as polyvinyl alcohol (PVA), polyurethane (PU), hydrogels, etc.). However, existing technologies (such as aerogel fibers prepared by freeze-drying) typically require the construction of a loose, porous, multi-level conductive structure within the fiber matrix to achieve high sensitivity. Because conventional flexible polymers are highly susceptible to severe densification and collapse when dried at room temperature due to strong capillary contraction forces and intermolecular hydrogen bonding, existing processes are forced to rely heavily on energy-intensive and inefficient freeze-drying techniques to maintain porosity. While this loose aerogel structure facilitates water molecule diffusion, it directly results in a lack of a high-strength load-bearing framework within the fiber, leading to insufficient mechanical strength and toughness, which cannot meet the stress requirements of subsequent spinning, weaving, and other processing.

[0004] Currently, the field still faces the following technical bottlenecks: (1) It is difficult to balance the electrical stability and mechanical properties of fibers. To achieve rapid wet response, fibers must have a porous structure, but this will directly weaken the mechanical properties. To improve strength, it is usually necessary to add dense coating to the outer layer of the fiber or add a large amount of filler to the matrix, which not only easily causes stress concentration and reduces toughness, but also seriously blocks the moisture transmission channel, resulting in a decrease in sensing sensitivity and reliability. (2) The structure and stability are seriously poor under high humidity conditions. Hydrophilic matrix materials are the basis for fiber response to humidity changes, but traditional porous or aerogel sensing fibers are very easy to destroy the original weak bonding force at the molecular level after absorbing moisture. Due to the lack of a stable dynamic cross-linking network support, fibers are very easy to undergo irreversible structural collapse or swelling deformation in high humidity environment, resulting in a sharp decline in mechanical properties and extremely poor sensing repeatability. (3) The preparation process is complex and difficult to carry out large-scale continuous production. Most current humidity sensing fibers involve complex processes such as chemical modification, multi-step coating, or harsh post-treatment (e.g., ultra-low temperature freeze drying that takes tens of hours), which are costly and difficult to achieve continuous and uniform spinning, thus limiting the development and application of the corresponding fiber materials. Summary of the Invention

[0005] The technical problem this invention aims to solve is to provide a reversible humidity-responsive sensing fiber, its preparation method, and its applications. This invention avoids reliance on freeze-drying processes by employing core-shell component-specific structural design, synergistic effects of polymer side-group steric hindrance and dynamic cross-linking networks, and unique DMSO / water bidirectional diffusion-induced coaxial wet spinning interface fusion and phase separation kinetics control. The goal is to construct a novel fiber that balances micro-nano interconnected pores with a high-strength fused node framework under conventional room temperature drying conditions, overcoming the challenge of balancing sensitivity and mechanical properties in existing humidity-sensing fibers. This aims to promote the development and technological advancement of such smart fiber materials and related electronic fabrics, laying the foundation and providing new methods for their application.

[0006] This invention provides a method for preparing reversible humidity-responsive sensing fibers, comprising the following steps:

[0007] (1) Dissolve aramid fibers in a solvent system to obtain a shell spinning solution;

[0008] (2) Mix the nematic MXene aqueous dispersion, the aqueous solution of the cellulose derivative containing substituted side groups and the solvent to obtain the core spinning solution; wherein the solvent is dimethyl sulfoxide (DMSO);

[0009] (3) The shell spinning solution and the core spinning solution are coaxially wet-spun and then post-treated to obtain humidity sensing fiber; wherein the coagulation bath used in the coaxial wet spinning is a borate aqueous solution; wherein the post-treatment includes soaking the fiber obtained by coaxial wet spinning in the coagulation bath, washing and drying at room temperature.

[0010] Preferably, the solvent system in step (1) includes an alkaline solution and dimethyl sulfoxide (DMSO); wherein the alkaline solution includes either an aqueous solution of potassium hydroxide or an aqueous solution of sodium hydroxide; and the concentration of the shell spinning solution is 0.01% to 5 wt%.

[0011] Furthermore, the dissolution of aramid fibers in the solvent system includes: pretreating the aramid fibers in an alkaline solution for 5-35 seconds, then adding dimethyl sulfoxide (DMSO) and stirring under sealed conditions for 5-8 days.

[0012] The aramid fibers include DuPont Kevlar fibers.

[0013] Preferably, the cellulose derivative containing substituted side groups in step (2) is one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.

[0014] Preferably, the solvent in step (2) is dimethyl sulfoxide (DMSO); the volume ratio of DMSO to water in the core layer solution is 1:20 to 2:1.

[0015] Preferably, in step (2), the mass ratio of cellulose derivative to MXene is 1:100 to 1:1.

[0016] In step (2), the nematic MXene aqueous dispersion has highly ordered pre-orientation of the internal sheets.

[0017] The MXene includes T3C2T X Where T represents a surface end group, which includes one or more of –OH, –O, and –F, and x represents the content of the surface end group, and x is not particularly limited.

[0018] The preparation of the nematic MXene aqueous dispersion in step (2) includes: centrifuging the MXene aqueous dispersion at 3500-5500 rpm for 10-40 minutes at 18 °C, discarding part of the supernatant, collecting the bottom dispersed phase, and obtaining the nematic MXene aqueous dispersion.

[0019] Preferably, in step (2), the concentration of the nematic MXene aqueous dispersion is 10-70 mg / mL; and the concentration of the aqueous solution containing the substituted side group of the cellulose derivative is 5-50 mg / mL.

[0020] Preferably, the mixing in step (2) is stirring, wherein the stirring speed is 100 ~ 1000 rpm and the stirring time is 100 ~ 5000 s.

[0021] Preferably, in step (3), the borate is one or more of sodium borate, potassium borate, and ammonium borate; and the concentration of the borate aqueous solution is 1~60 mg / mL.

[0022] Furthermore, the borates include, but are not limited to, one or more of sodium tetraborate decahydrate, sodium tetraborate pentahydrate, anhydrous sodium tetraborate, sodium metaborate, potassium tetraborate, potassium pentaborate, ammonium tetraborate, and ammonium pentaborate.

[0023] Preferably, the coaxial wet spinning in step (3) includes: extruding the core spinning solution and the shell spinning solution into a coagulation bath respectively, and cross-linking and molding them under dynamic stretching or rotation receiving action; wherein the core extrusion speed is 1~20 mL / h, and the shell extrusion speed is 1~60 mL / h.

[0024] Preferably, the rotating receiving linear speed is 0.1~10 m / min; the draw ratio is 1.0001~3 times.

[0025] The spinning process uses a rotating receiving or solidification drawing trough.

[0026] Preferably, the fibers obtained by coaxial wet spinning in step (3) are soaked in a coagulation bath for 1-24 hours.

[0027] In step (3), the washing process involves washing with an ethanol / water mixture 1 to 10 times.

[0028] In step (3), room temperature drying refers to naturally hanging or ventilating the washed fibers at room temperature. In this invention, there is no need for freeze-drying. Driven by the capillary contraction force of room temperature drying, the shell aramid nanofibers spontaneously and tightly interweave, forming high-strength "web-like" physical fusion nodes in local areas as stress transmission hubs. Relying on the spatial steric hindrance effect of the core macromolecular side groups and the rigid support of the cross-linked network, the excessive densification of the overall structure is effectively resisted, so that a large number of interconnected micro-nano pores are retained between the fiber core and shell.

[0029] The present invention provides a reversible humidity-responsive sensing fiber prepared by any of the methods described above. The humidity-sensitive fiber has a core layer and a shell layer structure, wherein the core layer has a highly oriented structure along the fiber axis, the shell layer has a tightly interwoven micro-nano porous network structure, and the internal network of the shell layer has locally dense fused nodes.

[0030] This invention provides an application of the reversible humidity-responsive sensing fiber in the fields of Internet of Things, smart wearables, medical and health care, industrial monitoring, or special equipment.

[0031] Preferably, the applications in the Internet of Things field include: smart agriculture humidity monitoring or smart home sensing devices.

[0032] Preferably, the applications in the field of smart wearables include: smart bracelets, smart sportswear, or smart masks.

[0033] Preferably, the applications in the medical and health field include: physiological monitoring equipment, intelligent wound dressings, or humidity warning devices. Preferably, the applications in the industrial monitoring or special equipment field include: humidity warning systems for buildings or enclosed spaces.

[0034] Beneficial effects

[0035] (1) The dense orientation structure induced by nematic liquid crystal overcomes the mechanical shortcomings of traditional aerogel fibers: The core layer of this invention introduces a nematic MXene dispersion with hydrodynamic pre-orientation properties. Combined with the shear orientation and dynamic stretching effects inside the spinneret and at the outlet during wet spinning, the core layer MXene nanosheets and macromolecular chains are efficiently oriented and highly aligned along the axial direction. This orientation structure not only constructs a continuous electron tunneling path, but also endows the fiber with high tensile strength, making up for the fatal defect of porous sensing fibers being easily broken under stress, and meeting the stringent textile processing requirements.

[0036] (2) Synergistic Construction of Anti-shrinkage Network by Spatial Hindrance and Dynamic Crosslinking: Unlike existing technologies that rely on high-energy-consuming freeze-drying processes to prevent pore collapse, this invention uses cellulose derivatives with large substituted side groups. Utilizing the strong steric hindrance effect of these side groups, combined with a highly efficient dynamic crosslinking network constructed using a slightly alkaline borate coagulation bath, the core layer macromolecular network achieves extremely strong compressive rigidity. During room temperature drying, it can resist strong capillary contraction forces, thus preserving abundant moisture transport microchannels.

[0037] (3) Mild coagulation and capillary force drive the construction of a porous fused shell: This invention abandons the acid / strong salt coagulation bath and adopts a slightly alkaline borate system to avoid the formation of a dense water-blocking "dead skin" during the phase separation of the aramid nanofibers (ANF) in the shell. Under the capillary force drive of natural drying, the ANF interweaves into a three-dimensional micro-nano porous network, and strong hydrogen bond recombination occurs at the contact points to form extremely stable "web-like fused nodes". This not only allows external water molecules to penetrate and diffuse rapidly, but also forms dense fused nodes to act as a load-bearing network, achieving an effective balance between rapid humidity response and high strength and toughness.

[0038] (4) Core-shell interface reinforcement design to achieve structural stability: By introducing DMSO into the aqueous phase system of the core layer containing sodium carboxymethyl cellulose or other cellulose derivatives with hydrophilic or ionic substituents and MXene, not only are the rheological properties of the core layer spinning solution adjusted, but also, at the moment of coaxial spinning, the rapid internal and external displacement and bidirectional diffusion of DMSO achieves the deep entanglement and "riveting" effect of the macromolecular chains of the core layer and shell layer (aramid nanofiber system), fundamentally solving the problem of easy delamination and detachment of the coaxial spinning interface of heterogeneous materials. Attached Figure Description

[0039] Figure 1 This is a scanning electron microscope image of the surface of the humidity sensing fiber in Example 1;

[0040] Figure 2 The stress-strain curve of the humidity sensing fiber in Example 1;

[0041] Figure 3 The curve showing the dynamic resistance change of the humidity sensing fiber in Example 1 as the relative humidity of the environment increases from 40% to 60% and then back to 40% is shown.

[0042] Figure 4 The stress-strain curve of the humidity sensing fiber in Example 2;

[0043] Figure 5 The curve showing the dynamic resistance change of the humidity sensing fiber in Example 2 as the relative humidity of the environment increases from 40% to 60% and then back to 40%;

[0044] Figure 6 The stress-strain curve of the humidity sensing fiber in Example 3;

[0045] Figure 7 The curve showing the dynamic resistance change of the humidity sensing fiber in Example 3 as the relative humidity of the environment increases from 40% to 60% and then back to 40%.

[0046] Figure 8 The stress-strain curve of the humidity sensing fiber in Comparative Example 1 is shown.

[0047] Figure 9 The curve showing the dynamic resistance change of the humidity sensing fiber in Comparative Example 1 as the relative humidity of the environment increases from 40% to 60% and then back to 40%.

[0048] Figure 10 The stress-strain curve of the humidity sensing fiber in Comparative Example 2 is shown.

[0049] Figure 11 The curve showing the dynamic resistance change of the humidity sensing fiber in Comparative Example 2 as the relative humidity of the environment increases from 40% to 60% and then back to 40%.

[0050] Figure 12 The stress-strain curves of the humidity sensing fiber in Comparative Example 3 are shown.

[0051] Figure 13 The curve showing the dynamic resistance change of the humidity sensing fiber in Comparative Example 3 as the relative humidity of the environment increases from 40% to 60% and then back to 40%.

[0052] Figure 14 The stress-strain curves of the humidity sensing fiber in Comparative Example 4 are shown.

[0053] Figure 15 The curve shows the dynamic resistance change of the humidity sensing fiber in Comparative Example 4 as the relative humidity of the environment increases from 40% to 60% and then back to 40%. Detailed Implementation

[0054] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0055] I. Relevant Testing Methods:

[0056] (1) Method for testing fiber cross-sectional area: Using Image-pro Plus 5.0 image analysis software, the cross-sectional area (mm²) of the fiber was calculated by referring to the scale of the electron microscope image of the fiber cross-section. 2 ).

[0057] (2) Test method for fiber mechanical properties: 20 humidity sensing fibers were randomly selected, fixed on a smooth plastic plate, and placed under standard atmospheric conditions for 24 hours to equilibrate; then, the tensile mechanical properties of each specimen were tested using a universal testing machine. The test parameters were: clamping distance l0 was 20 mm, clamping tensile rate was 30 mm / min. -1 The pre-tension was 0.1 cN, and the stress-strain curves for each specimen were obtained. The fiber's breaking strength P... f The formulas for calculating elongation at break ε are as follows:

[0058] , ;

[0059] In the formula: F i A: Breaking strength of the i-th fiber (in N); A: Cross-sectional area of ​​the fiber (in mm²) 2 ); l i : The breaking length of the i-th fiber (in mm); l0: The initial length of the fiber (20 mm).

[0060] (3) Determination of initial resistance and resistance change rate under different humidity conditions of the fiber: The fiber was cut to a length of 3 cm, with 0.5 cm left at each end. Both ends were glued to a 1 cm × 0.5 cm single-sided conductive tape. Liquid metal was applied to the connection between the fiber and the tape to ensure full contact between the fiber and the tape. Then, another layer of conductive tape of the same size was sealed. The initial resistance was measured using a data acquisition and recording multimeter (DAQ6510, Keithley, USA). The prepared sample was fixed on a custom-made glass stage. A cover connected to the humidifier tube was placed over the fiber to create a high humidity environment. The humidity was reduced by removing the cover (the humidity was adjusted by the size of the cover and the mist output of the humidifier). During the process, the resistance signal at both ends of the fiber was recorded using a data acquisition and recording multimeter (DAQ6510, Keithley, USA), and the resistance change rate was calculated.

[0061] Resistance change rate (%) = ΔR / R0 × 100% = (R - R0) / R0 × 100%;

[0062] In the formula, R is the real-time resistance of the fiber; R0 is the initial resistance of the fiber; and ΔR is the relative change in fiber resistance.

[0063] II. Preparation of Aramid Nanofiber Dispersion and MXene Aqueous Dispersion:

[0064] (1) Preparation method of aramid nanofiber dispersion in the examples: Add 0.3 g KOH to 0.8 g deionized water until completely dissolved and mixed evenly, and cool the solution to room temperature. Then, immerse DuPont Kevlar fibers (PPTA) of different masses into the above KOH / H2O solution and pretreat for 15 seconds. Add dimethyl sulfoxide to the PPTA / KOH / H2O mixture, seal the container and magnetically stir at 400 rpm for 7 days at room temperature to obtain uniform aramid nanofiber spinning solutions of different concentrations.

[0065] (2) Preparation methods of MXene aqueous dispersion and nematic aqueous dispersion in the examples: 3.2 g of weighed lithium fluoride was added to the reaction vessel, and 40 mL of 9 mol / L hydrochloric acid was added to the reaction vessel. The mixture was stirred at 40 °C for 48 hours. The product after reaction was poured into a centrifuge tube. The centrifuge tube was placed in a centrifuge with the speed adjusted to 5000 rpm and centrifuged for one minute. The centrifuge tube was removed, the supernatant was discarded, and deionized water was repeatedly added to the precipitate to wash the acidic dispersion. The mixture was centrifuged repeatedly at 5000 rpm for one minute each time until the pH of the mixture was neutral (~6). Then, centrifugation was continued to allow the product to fully peel off and swell in water. The stable supernatant was collected to obtain the MXene nanosheet aqueous dispersion.

[0066] Further, the above MXene aqueous dispersion was centrifuged at 4500 rpm for 30 minutes at 18 °C, and part of the supernatant was discarded, collecting the high-concentration viscous dispersed phase at the bottom. The MXene nanosheets in this high-concentration dispersed phase have a high degree of orientation, thus obtaining a nematic MXene nanosheet aqueous dispersion.

[0067] Example 1

[0068] The method for preparing the humidity sensing fiber in this embodiment is as follows:

[0069] A 10 mg / mL aramid nanofiber dispersion (0.9 wt%) was used as the shell spinning solution and stirred at 1000 rpm for 20 min using a planetary stirrer to remove bubbles before use.

[0070] A 40 mg / mL aqueous dispersion of nematic MXene nanosheets and a 30 mg / mL aqueous dispersion of sodium carboxymethyl cellulose (CMC) (Shanghai Yuanye Biotechnology Co., Ltd.) were mixed thoroughly using a planetary stirrer at 1000 rpm for 20 min. Then, DMSO (DMSO to water volume ratio of 1:4) was added and the mixture was stirred thoroughly using a planetary stirrer at 1000 rpm for 20 min. The resulting solution was used as the core spinning solution (MXene to CMC mass ratio of 9:1).

[0071] Subsequently, the spinning solutions of the shell layer and the core layer were extruded through a coaxial spinning needle into a coagulation bath containing a 4 mg / mL sodium tetraborate aqueous solution (Shanghai Leyan Biotechnology Co., Ltd.) at speeds of 30 mL / h and 6 mL / h, respectively (the rotational receiving linear speed of the coagulation bath was 1.5 m / min; the corresponding draw ratio was 1.05 times). After soaking in the coagulation bath for 1 h, the fibers were transferred to an ethanol / water (ethanol to water volume ratio of 1:3) washing solution and washed 3 times. The fibers were then dried at room temperature to obtain humidity sensing fibers (also known as reversible humidity response sensing fibers).

[0072] The humidity sensing fiber has a tensile strength of 356 MPa and an elongation at break of 9% (e.g., ...). Figure 2 As shown), the initial resistivity of the core layer is 50 Ω·cm. -1 The humidity sensing fiber exhibits a reversible resistance response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the ambient relative humidity changes from 40% to 60%, the resistance of the humidity sensing fiber increases, with a resistance change rate of 24% and a response time of approximately 1.8 seconds. When the ambient relative humidity returns from 60% to 40%, the fiber resistance can return to near its initial value, with a recovery time of approximately 14 seconds. Figure 3 (As shown).

[0073] Example 2

[0074] The preparation method of the humidity sensing fiber (i.e., the reversible humidity response sensing fiber) in this embodiment is basically the same as that in Example 1, except that the sodium tetraborate aqueous solution coagulation bath is replaced with a potassium tetraborate aqueous solution coagulation bath.

[0075] Performance testing showed that the humidity sensing fiber had a tensile strength of 386 MPa and an elongation at break of 9% (e.g., ...). Figure 4 As shown), the initial resistivity of the core layer is 53 Ω·cm. -1 The humidity-sensing fiber exhibits a reversible resistive response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the ambient relative humidity changes from 40% to 60%, the fiber resistance increases, with a resistance change rate of 23% and a response time of approximately 1.7 seconds. When the ambient relative humidity returns from 60% to 40%, the fiber resistance returns to near its initial value, with a recovery time of approximately 17 seconds. Figure 5 (As shown).

[0076] Example 3

[0077] The method for preparing the humidity sensing fiber in this embodiment is as follows:

[0078] A 10 mg / mL aramid nanofiber dispersion (0.9 wt%) was used as the shell spinning solution and stirred at 1000 rpm for 20 min using a planetary stirrer to remove bubbles before use.

[0079] A 40 mg / mL aqueous dispersion of nematic MXene nanosheets and a 30 mg / mL aqueous dispersion of hydroxyethyl cellulose (Shanghai Yuanye Biotechnology Co., Ltd.) were mixed thoroughly using a planetary stirrer at 1000 rpm for 20 min. Then, DMSO (DMSO to water volume ratio of 1:4) was added and the mixture was stirred thoroughly using a planetary stirrer at 1000 rpm for 20 min. The resulting solution was used as the core spinning solution (MXene to hydroxyethyl cellulose mass ratio of 9:1).

[0080] Subsequently, the spinning solutions of the shell layer and the core layer were extruded through a coaxial spinning needle at speeds of 30 mL / h and 6 mL / h, respectively, into a 4 mg / mL sodium tetraborate aqueous solution (Shanghai Leyan Biotechnology Co., Ltd.) drawing and coagulation bath (drawing ratio of 1.05). After soaking in the coagulation bath for 1 h, the fibers were transferred to an ethanol / water (ethanol to water volume ratio of 1:3) washing solution and washed 3 times. The fibers were then dried at room temperature to obtain humidity sensing fibers (also known as reversible humidity response sensing fibers).

[0081] Performance testing showed that the humidity sensing fiber has a tensile strength of 336 MPa and an elongation at break of 10% (e.g., ...). Figure 6As shown), the initial resistivity of the core layer is 56 Ω·cm. -1 The humidity-sensing fiber exhibits a reversible resistive response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the ambient relative humidity changes from 40% to 60%, the fiber resistance increases, with a resistance change rate of 22% and a response time of approximately 1.5 seconds. When the ambient relative humidity returns from 60% to 40%, the fiber resistance returns to near its initial value, with a recovery time of approximately 25.5 seconds. Figure 7 (As shown).

[0082] Comparative Example 1

[0083] The preparation method of the humidity sensing fiber in this comparative example is basically the same as that in Example 1, except that the fiber core layer does not contain sodium carboxymethyl cellulose, as detailed below:

[0084] A 10 mg / mL aramid nanofiber dispersion (0.9 wt%) was used as the shell spinning solution and stirred at 1000 rpm for 20 min using a planetary stirrer to remove bubbles before use.

[0085] DMSO (DMSO to water volume ratio of 1:4) was added to a 40 mg / mL aqueous dispersion of nematic MXene nanosheets, and the mixture was stirred at 1000 rpm for 20 min using a planetary stirrer to obtain a homogeneous solution, which was then used as the core spinning solution. Subsequently, the shell and core spinning solutions were extruded through a coaxial spinning needle at speeds of 30 mL / h and 6 mL / h, respectively, into a coagulation bath containing a 4 mg / mL sodium tetraborate aqueous solution (Shanghai Leyan Biotechnology Co., Ltd.) (the rotational receiving linear velocity of the coagulation bath was 1.5 m / min; the corresponding draw ratio was 1.05). After soaking in the coagulation bath for 1 h, the fibers were transferred to an ethanol / water (ethanol to water volume ratio of 1:3) washing solution and washed three times. The fibers were then dried at room temperature under ventilation to obtain humidity sensing fibers.

[0086] Due to the lack of sodium carboxymethyl cellulose, the cross-linking between the internal components of the fiber is insufficient. Performance testing showed that the fiber's breaking strength decreased to 330 MPa, and the elongation at break was 8% (e.g., ...). Figure 8 As shown), the initial resistivity of the core layer increased to 60 Ω·cm. -1 The humidity-sensing fiber exhibits an irreversible resistive response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the ambient relative humidity changes from 40% to 60%, the fiber resistance increases, the rate of change of resistance decreases to 20%, and the response time extends to about 3 seconds. When the ambient relative humidity returns from 60% to 40%, due to insufficient cross-linking leading to irreversible changes in the microstructure, the fiber resistance cannot return to near its initial value (e.g., ...). Figure 9 (As shown).

[0087] Comparative Example 2

[0088] The preparation method of the humidity sensing fiber in this comparative example is basically the same as that in Example 1, except that the sodium tetraborate aqueous solution coagulation bath is replaced with a pure aqueous solution coagulation bath.

[0089] Due to the lack of sodium tetraborate, sodium carboxymethyl cellulose and MXene in the fiber core cannot form a dense dynamic cross-linked network of borate esters. They rely only on physical entanglement and weak hydrogen bonds, resulting in uneven shrinkage during fiber drying, poor structural uniformity and density, and collapse of moisture transport channels.

[0090] Performance testing showed that the fiber breaking strength decreased to 230 MPa, and the elongation at break was 8% (e.g., Figure 10 As shown), the initial resistivity of the core layer increased to 65 Ω·cm. -1 The humidity-sensing fiber exhibits an irreversible resistive response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the relative humidity changes from 40% to 60%, the fiber resistance increases, the rate of change of resistance decreases to 19%, and the response time extends to approximately 2.3 seconds. When the relative humidity returns from 60% to 40%, the lack of a reversible cross-linking network hinders moisture removal, and the fiber resistance cannot return to near its initial value (e.g., ...). Figure 11 (As shown).

[0091] Comparative Example 3

[0092] The preparation method of the humidity sensing fiber in this comparative example is basically the same as that in Example 1, except that the sodium tetraborate aqueous solution coagulation bath is replaced with a coagulation bath containing a mixed aqueous solution of 0.06 wt% boric acid and 25 wt% tert-butanol.

[0093] Because boric acid is a weak acid, its degree of dissociation in aqueous solution is extremely low, making it difficult to form sufficient borate crosslinking sites. Compared to sodium tetraborate, the dynamic crosslinking efficiency between borate and CMC and other hydroxyl-containing components in the system is significantly reduced, resulting in insufficient crosslinking of the core layer macromolecular network, weak interlayer bonding, and an inability to fully exert synergistic reinforcement and stress transfer effects.

[0094] Performance testing showed that the fiber breaking strength decreased to 207 MPa and the breaking elongation decreased to 7% (e.g., Figure 12 As shown), the initial resistivity of the core layer increased to 85 Ω·cm. -1 The humidity sensing fiber exhibits an irreversible resistive response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the ambient relative humidity changes from 40% to 60%, the fiber resistance increases, the resistance change rate decreases to 18%, and the response time extends to approximately 37 seconds. When the ambient relative humidity returns from 60% to 40%, the fiber resistance cannot return to near its initial value (e.g., ...). Figure 13 (As shown).

[0095] Comparative Example 4

[0096] The preparation method of the humidity sensing fiber in this comparative example is basically the same as that in Example 1, except that the CMC of the core layer is replaced with polyvinyl alcohol (PVA).

[0097] Because PVA molecular chains are highly flexible and contain a large number of continuous hydroxyl groups, when the fiber is dried at room temperature without freeze drying, the strong capillary contraction force and the strong hydrogen bonding between the polymer chains will cause severe volume shrinkage and structural densification, resulting in the collapse of internal micropores and a lack of effective moisture transport and desorption channels.

[0098] Performance testing showed that the fiber breaking strength decreased to 138 MPa, and the elongation at break was 11% (e.g., ...). Figure 14 As shown), the initial resistivity of the core layer increased to 120 Ω·cm. -1 The humidity sensing fiber exhibits an irreversible resistive response during the humidity switching process from 40%RH to 60%RH and back to 40%RH. When the ambient relative humidity changes from 40% to 60%, the fiber resistance increases, the rate of change of resistance decreases to 19%, and the response time becomes delayed to approximately 55 seconds. When the ambient relative humidity returns from 60% to 40%, the fiber resistance cannot return to near its initial value (e.g., ...). Figure 15 (As shown).

[0099] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a reversible humidity-responsive sensing fiber, characterized in that, Includes the following steps: (1) Dissolve aramid fibers in a solvent system to obtain a shell spinning solution; (2) Mix the nematic MXene aqueous dispersion, the aqueous solution of the cellulose derivative containing substituted side groups and the solvent to obtain the core spinning solution; wherein the solvent is dimethyl sulfoxide (DMSO); (3) The shell spinning solution and the core spinning solution are coaxially wet-spun and then post-treated to obtain humidity sensing fiber; wherein the coagulation bath used in the coaxial wet spinning is a borate aqueous solution; wherein the post-treatment includes soaking the fiber obtained by coaxial wet spinning in the coagulation bath, washing and drying at room temperature.

2. The preparation method according to claim 1, characterized in that, The solvent system in step (1) includes an alkaline solution and dimethyl sulfoxide (DMSO); wherein the alkaline solution includes either an aqueous solution of potassium hydroxide or an aqueous solution of sodium hydroxide; and the concentration of the shell spinning solution is 0.01% to 5 wt%.

3. The preparation method according to claim 1, characterized in that, The cellulose derivative containing substituted side groups in step (2) is one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.

4. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of cellulose derivative to MXene is 1:100 to 1:1; In step (2), the concentration of the nematic MXene aqueous dispersion is 10-70 mg / mL; the concentration of the aqueous solution of the cellulose derivative containing substituted side groups is 5-50 mg / mL.

5. The preparation method according to claim 1, characterized in that, In step (3), the borate is one or more of sodium borate, potassium borate, and ammonium borate; the concentration of the borate aqueous solution is 1~60 mg / mL.

6. The preparation method according to claim 1, characterized in that, The coaxial wet spinning in step (3) includes: extruding the core spinning solution and the shell spinning solution into a coagulation bath respectively, and cross-linking and forming under dynamic stretching or rotation receiving action; wherein the core extrusion speed is 1~20 mL / h, and the shell extrusion speed is 1~60 mL / h.

7. The preparation method according to claim 6, characterized in that, The rotational receiving linear speed is 0.1~10 m / min; the draw ratio is 1.0001~3 times.

8. The preparation method according to claim 1, characterized in that, The fibers obtained by coaxial wet spinning in step (3) are soaked in a coagulation bath for 1-24 hours.

9. A reversible humidity-responsive sensing fiber prepared by the method according to any one of claims 1-8, characterized in that, The reversible humidity-responsive sensing fiber has a core layer and a shell layer structure, wherein the core layer has a highly oriented structure along the fiber axis, and the shell layer has a tightly interwoven micro-nano porous network structure, and the internal network of the shell layer has locally dense fused nodes.

10. The application of the reversible humidity-responsive sensing fiber of claim 9 in the fields of Internet of Things, smart wearables, medical and health care, industrial monitoring or special equipment.